Clinical significance of HIV-associated bone loss: when and how to intervene. (September 2008) - Yin, Michael T; Shane, Elizabeth; Anastos, Kathryn
Moderate decreases in bone mineral density (BMD) occur after initiation of several antiretroviral regimens. However, BMD appears to stabilize over time. Alendronate and zoledronate therapy decreases bone turnover markers and increases BMD in HIV-positive subjects with low BMD. Low BMD is a common problem, but whether this translates into increased incidence or prevalence of fragility fractures is uncertain. Screening and treatment of osteoporosis in HIV-positive individuals should follow guidelines for the general population. When there is a strong indication to treat, bisphosphonates should be considered as first-line therapy as studies have demonstrated their short-term efficacy for increasing BMD and their tolerability in HIV-infected individuals. In this article, we review recent publications on bone loss, fractures and treatment of osteoporosis in HIV-positive individuals.